Faktor-Faktor yang Berhubungan dengan Perilaku dan Motivasi Masyarakat terhadap Pertolongan Pertama pada Korban Kecelakaan Lalu Lintas - Madani, Ultra; Firdaus, Syamsul; Syafwani, M.; Hiryadi, Hiryadi; Sary, Era Widia (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
for traffic accident victims. The method used is quantitative research with a cross-sectional approach. The research results show that the most dominant gender factor is related to people's behavior toward first aid for traffic accident victims, with an OR value of 78.3. Meanwhile, the most dominant knowledge factor relates to people's motivation for first aid for traffic accident victims, with an OR value of 11.5. In conclusion, knowledge can motivate people to carry out first aid. Therefore, it is necessary to provide counseling, training, and assistance in improving community behavior and motivation in first aid to traffic accident victims. Keywords: Traffic Accidents, Motivation, Behavior, First Aid